Distribuição da evaporação no interior de um ambiente protegido - Jadoski, Cleber Junior [UNESP]; Klar, Antonio Evaldo [UNESP]; Maggi, Marcio Furlan; Ramiro, Juliana [UNESP]; dos Santos, Alexandre Barreto Almeida [UNESP]; Fulan, Samuel Rodrigues [UNESP] (My University, 2006)
This work aimed to study evaporation distribution in a protected environment. The experiment was set up in polyethylene greenhouse at the Lageado Experimental Farm in the School of Agronomic Sciences (FCA, UNESP-Botucatu) in the winter of 2005. 132 500-ml plastic micro evaporimeters (13.7 diameter) were used used to obtain evaporation values and analyze spatial energy distribution. These micro evaporimeters were distributed in 44 equidistant points, at three different heights from the soil surface: 0.40, 0.80 and 1.20cm The tunnel-type greenhouse was 7.5 m wide, 27.5 m long and 3.20 m high at the center, and was covered with black shadow screen (sombrite) on the sides. Southeast/northwest orientation, based on true north, was used foro othe greenhouse longitudinal axis. For variable comparison, a geostatistics was used through the □GS+ program. From obtained data, it was concluded that: there was spatial variability at different points and heights of the microevaporation values obtained from micro evaporimeters were not greenhouse; the Class A Pan installed outside the greenhouse can be used to evaluate the internal evaporation.
Evaporation distribution in a protected environment
Keywords: Class A pan; Geostatistics; Microevaporimeter